Understanding Assessment Processes for Communicative Competence through an Analysis of Teachers' Reported Practice - Fernando Guzmán-Simón; Juan Jesús Torres-Gordillo; Katia Caballero (MDPI AG, 2020)
This research addresses the types of assessment tasks, the assessment criteria, instruments and procedures of communicative competence used by primary school teachers in Andalusia. This multiple-case study drew on the experiences of teachers from four schools in the south of Spain. The data source has been the focus groups in which the teachers took part. The transcripts were analysed thematically by three researchers who devised a system of categories designed through an iterative process. The findings reveal the paucity of tasks used to assess reading, listening and oral expression. The study also shows the diverse problems faced by teachers when it comes to evaluating communicative competence. This paper highlights the need to rethink the curricular contents and the methods applied to assess communicative competence in primary schools.